Perceptions of the Targets and Sources of COVID-19 Threat are Structured by Group Memberships and Responses are Influenced by Identification with Humankind. Issue 1 (16th March 2022) - Frenzel, Svenja B.; Junker, Nina M.; Avanzi, Lorenzo; Erkens, Valerie A.; Haslam, S. Alexander; Haslam, Catherine; Häusser, Jan A.; Knorr, Daniel; Meyer, Ines; Mojzisch, Andreas; Monzani, Lucas; Reicher, Stephen D.; et al.
The purpose of this study was to investigate which social groups are perceived as a threat target and which are perceived as a threat source during the COVID-19 outbreak. In a German sample ( N = 1454) we examined perceptions of social groups ranging from those that are psychologically close and smaller (family, friends, neighbors) to those that are more distal and larger (people living in Germany, humankind). We hypothesized that psychologically closer groups would be perceived as less affected by COVID-19 as well as less threatening than more psychologically distal groups. Based on social identity theorizing, we also hypothesized that stronger identification with humankind would change these patterns. Furthermore, we explored how these threat perceptions relate to adherence to COVID-19 health guidelines. In line with our hypotheses, latent random-slope modelling revealed that psychologically distal and larger groups were perceived as more affected by COVID-19 and as more threatening than psychologically closer and smaller groups. Including identification with humankind as a predictor into the threat target model resulted in a steeper increase in threat target perception patterns, whereas identification with humankind did not predict differences in threat source perceptions. Additionally, an increase in threat source perceptions across social groups was associated with more adherence to health guidelines, whereas an increase in threat target perceptions was not. We fully replicated these findings in a subgroup from the original sample ( N = 989) four weeks later. We argue that societal recovery from this and other crises will be supported by an inclusive approach informed by a sense of our common identity as human beings.